CD4 and CD8 T Cells Directly Recognize Murine Gammaherpesvirus 68-Immortalized Cells and Prevent Tumor Outgrowth - Liang, Xiaozhan (American Society for Microbiology, 2013)
There has been extensive research regarding T cell recognition of Epstein-Barr virus-transformed cells; however, less is known regarding the recognition of B cells immortalized by gamma-2 herpesviruses. Here we show that B cells immortalized by murine gammaherpesvirus 68 (MHV-68, γHV-68) can be controlled by either CD4 or CD8 T cells in vivo. We present evidence for the direct recognition of infected B cells by CD4 and CD8 T cells. These data will help in the development of immunotherapeutic approaches combating gamma-2 herpesvirus-related disease.